2018
DOI: 10.3390/ijerph15071310
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Refined Kano Model and QFD for Service Quality Improvement in Healthy Fast-Food Chain Restaurants

Abstract: People are paying greater attention to health. To maintain a good health status and obtain food fast, customers may go to healthy fast-food chain restaurants such as Subway more often than before in China and Taiwan. Healthy fast-food chain restaurants come with a healthy spin, seeking to differentiate themselves from other fast-food restaurants. This paper combined the refined Kano model and the quality function deployment (QFD) method. The refined Kano model was used to understand how customers perceive serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 28 publications
0
37
0
3
Order By: Relevance
“…Previous research focused mainly on the factors influencing the choice of restaurants and other catering establishments, as well as school or university canteens. In general, the factors influencing consumer decisions about eating out are related to food (taste, cost, accessibility of food) and quality of services [ 23 , 24 ], not only to nutritional value [ 24 ]. Other authors stated that factors such as marketing and promotion, as well as price, are not so important [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research focused mainly on the factors influencing the choice of restaurants and other catering establishments, as well as school or university canteens. In general, the factors influencing consumer decisions about eating out are related to food (taste, cost, accessibility of food) and quality of services [ 23 , 24 ], not only to nutritional value [ 24 ]. Other authors stated that factors such as marketing and promotion, as well as price, are not so important [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the experience in ethnic restaurants is more important than the choice of food and as important as its quality [ 29 ], while hygiene is more important than food [ 30 , 31 , 32 ]. In the previous decade, introducing a healthy menu in catering establishments and taking diet into account were important factors in the decision-making process when choosing a dining place [ 23 , 26 , 33 , 34 ]. Jang et al [ 35 ] observed an important segment of consumers and called them “health-conscious consumers”.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study was conducted at Student Health Services of the Missouri University of Science and Technology, where the data were collected using the Kano survey [26]. Healthy fast-food chain restaurants sought to differentiate themselves from other fast-food restaurants and understand how customers perceive service attributes using the Kano Model [27].…”
Section: The Kano Model Used For Comparisonsmentioning
confidence: 99%
“…It can effectively help enterprises collect and realize customer demand [6].It has been widely used. For example, Liu and Zhang have applied QFD method to the development of creative products and achieved remarkable results; Chen, Yeh and other scholars [7] have used QFD to evaluate and improve the service quality of fast food chain restaurants; Liu, Cheng, Lee and Gau [8] also have applied QFD to studying industrial packaging for safe delivery. QFD technology focuses on the construction of quality house (HoQ), because HoQ can effectively link demand with technology [9].…”
Section: A Quality Function Deployment (Qfd)mentioning
confidence: 99%